2022
DOI: 10.3389/fonc.2022.831649
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Nomograms to Predict Overall Survival and Cancer-Specific Survival in Patients With Pancreatic Adenosquamous Carcinoma

Abstract: BackgroundPancreatic adenosquamous carcinoma (PASC) is a heterogeneous group of primary pancreatic cancers characterized by the coexistence of both glandular and squamous differentiation. The aim of this study was to develop nomograms to predict survival outcomes in patients with PASC.MethodsIn this retrospective study, data on PASC, including clinicopathological characteristics, treatments, and survival outcomes, were collected from the SEER database between 2000 and 2018. The primary endpoints were overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The tumor size of the vast majority of solid tumors, such as lung cancer and breast cancer, is included in their TNM stage system to assess prognosis; the larger the tumor, the worse the prognosis. [28,29] This finding is consistent with the results of the present study. However, the T stage of gastric cancer only includes the depth of tumor invasion, and if the tumor size is used together with the depth of tumor invasion to assess prognosis, it will lead to more precise treatment for patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The tumor size of the vast majority of solid tumors, such as lung cancer and breast cancer, is included in their TNM stage system to assess prognosis; the larger the tumor, the worse the prognosis. [28,29] This finding is consistent with the results of the present study. However, the T stage of gastric cancer only includes the depth of tumor invasion, and if the tumor size is used together with the depth of tumor invasion to assess prognosis, it will lead to more precise treatment for patients.…”
Section: Discussionsupporting
confidence: 93%
“…The tumor size of the vast majority of solid tumors, such as lung cancer and breast cancer, is included in their TNM stage system to assess prognosis; the larger the tumor, the worse the prognosis. [28,29] Table 3 Multivariate analysis of patients with metastatic gastric adenocarcinoma. This finding is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer stem cell hypothesis is considered to be the most likely pathogenic contributor, as reported in previous studies [ 12 , 13 ]. However, the association between the number of SCC components and the prognosis remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…ASCP is typically considered more aggressive than standard PDAC. Multiple registry studies that have evaluated large cohorts of patients concur that ASCP patients have similar demographic characteristics to PDAC patients, but present with larger and more poorly differentiated tumors [78][79][80][81] . Median survival in the unselected population is similar between ASCP and PDAC patients and is ~4-6 months [Table 2].…”
Section: Epidemiology and Prognosismentioning
confidence: 98%
“…Resection is recommended for patients with early-stage disease and several population-based studies have demonstrated a significant survival advantage for patients with locoregional disease who undergo surgery versus those who do not [79][80][81] . R1 resection was associated with worse outcomes in one smaller singleinstitution study that included only one patient with this resection status [50] , but no contribution of R0 status to survival was found in two larger population-based studies [78,80] .…”
Section: Resectable Diseasementioning
confidence: 99%